1987
DOI: 10.1007/bf02555426
|View full text |Cite
|
Sign up to set email alerts
|

Tissue oxygen tension as a predictor of colonic anastomotic healing

Abstract: Inadequate blood flow causing tissue hypoxia can result in failure of anastomotic healing. Tissue oxygen tension (ptO2) measurement has been used to predict anastomotic leakage in animals, but its use in humans has not been described previously. A Clark-type oxygen electrode was used to measure ptO2 on the colon of 50 patients undergoing colonic resection and anastomosis. Baseline ptO2 levels were lowest on the descending colon (31.8 +/- 7.4 mmHg, mean +/- SD) and tended to increase at all sites with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0
4

Year Published

1990
1990
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(103 citation statements)
references
References 13 publications
0
94
0
4
Order By: Relevance
“…The shift of bacterial communities from obligate to facultative anaerobes strongly suggests a disruption in anaerobiosis and points to a potential role for oxygen in intestinal dysbiosis (Rigottier-Gois 2013). Spatial variation of mucosal oxygen concentration was also implicated along the human colon, especially between the cecum and distal regions (Sheridan et al, 1987). The overgrowth of aerotolerant bacteria with ileal CD (Baumgart et al, 2007;Willing et al, 2009Willing et al, , 2010 was frequently found in several studies, wherein they indicated that the functional stability or disturbance of oxygen-microbe interaction through the intestine may be related to local intestinal health or dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…The shift of bacterial communities from obligate to facultative anaerobes strongly suggests a disruption in anaerobiosis and points to a potential role for oxygen in intestinal dysbiosis (Rigottier-Gois 2013). Spatial variation of mucosal oxygen concentration was also implicated along the human colon, especially between the cecum and distal regions (Sheridan et al, 1987). The overgrowth of aerotolerant bacteria with ileal CD (Baumgart et al, 2007;Willing et al, 2009Willing et al, , 2010 was frequently found in several studies, wherein they indicated that the functional stability or disturbance of oxygen-microbe interaction through the intestine may be related to local intestinal health or dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…The environmental drivers of the differences for both axes of variation cannot be determined from this study, but the trend follows the main physicochemical changes known to occur through the colorectum: lumen content dehydration and pH increase towards the rectum (Bown et al, 1974), as well as highest short-chain fatty acid, lactate and ethanol concentrations in the proximal colon, decreasing distally with a concomitant increase in products of protein fermentation (for example, ammonia, branched chain fatty acids and phenolic compounds) (Macfarlane et al, 1992). There is also one report of there being differences in mucosal oxygen concentration along the human colon, especially between the caecum and distal regions (pO 2 [mm Hg] being 33.7 ± 7.5 in the caecum, compared with 40.7 ± 8.2, 41.2 ± 8.7 and 39.7 ± 7.3 for the transverse colon, sigmoid colon and rectum, respectively (Sheridan et al, 1987)). Interestingly, recent studies linking a higher abundance of aerotolerant bacteria with ileal CD (Baumgart et al, 2007) and surgical intervention (Hartman et al, 2009) suggest that perturbations in oxygen concentration may be associated with the observed dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interposition of bioengineered substitutes organized in a tubular fashion, such as the gut, appear to be particularly prone to complications (Badylak, S. et al, 2000;Chen & Badylak, 2001;Thompson et al, 1986). Given that inadequate oxygen supply and decreased local microperfusion are believed to be at the origin of many adverse events in gastrointestinal surgery (Anegg et al, 2008;Attard et al, 2005;Sheridan et al, 1987), hypoxia and ischemia presumably account for anastomotic leakage and stricture formation after interposition of bioengineered tubular constructs. In recent years, considerable effort has been done to develop bioreactors that allow nourishment of growing tissue masses in vitro whose size exceeds the largest possible unit accessible to oxygen and nutrients by sole diffusion.…”
Section: Bioreactorsmentioning
confidence: 99%